RNA-BINDING PROTEINS IN DENDRITOGENESIS - Perycz, M; Parobczak, K; Jaworski, J (Acta neurobiologiae experimentalis, 2009)
Proper development of dendritic arbor is a precisely orchestrated process in which translation is shown to play pivotal role. RNA binding proteins such as ZBP1 (beta-actin zipcode binding protein 1), Staufenl and Staufen2 bind to and transport their target mRNAs, enabling their local translation in dendrites and taking part in regulation of this process. ZBP1 knockdown with short interfering RNAs in developing rat hippocampal neurons in vitro, resulted in decrease in total number of dendrites and dendritic tree complexity, which was reversed both with siRNA-resistant ZBP1 rescue mutant and jasplakinolide treatment that prevents depolymerisation of actin cytoskeleton. In contrast, mature neurons with stable dendritic arbors, did not lose dendrites upon ZBP1 depletion, which suggests ZBP1 plays role in formation of new dendrites as opposed to maintenance of mature ones. We also show that both Staufenl and Staufen2 knockdown in developing neurons results in impoverishment in dendritic arbors complexity and decrease in total number of dendrites. RNA-binding proteins can be subject to phosphorylation, which modulate their activity, and one possibility for a common regulator of their role in dendritogenesis would be Src kinase, which we show to phosphorylate ZBP1 and Staufenl. Taken together, presented data demonstrate that mRNA transport and possibly local protein synthesis play a prominent role in development of dendritic arbor.